(untitled) (Research, Society and Development, 2022)
Leprosy represents a serious public health problem, the disease causes permanent deformities and physical disabilities, for many years it has afflicted the population due to its high potential for contagion. Even after so much clarification about the pathology there are still religious beliefs and prejudices that probe the bearer causing loneliness, social isolation, depression and fear. In this sense, the present study aims to demonstrate, through the literature, the role and care provided by the Primary Care nurse in the control of leprosy. This is a bibliographic review research, of a descriptive nature, composed of 12 articles related to the theme and published between the years 2008 and 2017, in the virtual databases. At the end of the study, the importance of the nurse in the early diagnosis, prevention of deformities and in the continuity of the treatment was observed, where it has to execute strategies in a way that acquaints the population and breaks the "taboos" associated with the infection.